PENGARUH NHT BERBANTU MEDIA ULAR TANGGA UNTUK MENINGKATKAN MINAT BELAJAR - Nur Maria Ulfa; Aries Tika Damayani; Rofian Rofian (FKIP, PGSD, Universitas Slamet Riyadi, 2019)
This researched to determine and analyze the effect of the snake ladder media Numbered Head Together (NHT) learning model to increase the learning interest of Grade II students at SDN Menur Mranggen Demak. This type of research was quantitative in the form of Pre-Experimental Design with the type of One-Group Pretest-Posttest Design. Data obtained through observation, documentation, tests, questionnaires, and interviews. The background of this study is due to the lack of use of models and instructional media which results in less interesting learning and was an impact on students' interest in learning and student learning outcomes on Indonesian subjects. The results of the analysis of student learning interest questionnaire data showed that the average pretest was 57.88. After being treated with this learning model, the posttest mean increased to 71.70. While the analysis of student learning outcomes data obtained an average pretest value of 62.59 and the average posttest value of 79.62. The conclusion was that there is a significant influence on the snake ladder's Numbered Head Together (NHT) learning model to increase the interest in learning in class II SDN Menur Mranggen Demak.